A comprehensive review of the effect of lubricant on the flow characteristics of supercritical CO2 during cooling. (January 2022) - Xu, Wenjie; Li, Minxia; Li, Yang; Zhao, Jun
Highlights: First overview of the flow characteristics of CO2 -lubricant mixtures in gas coolers. Presents multiple factors affecting the flow characteristics of CO2 -lubricant mixtures. Reviews the analysis models of the flow and heat transfer of CO2 -lubricant mixtures. Comments on pressure drop correlations of CO2 -lubricant mixtures. Recommendations for future studies on the CO2 -lubricant mixture flow characteristics. Abstract: With the recent advancements in designs and optimization of gas coolers in CO2 transcritical refrigeration and heat pump systems, the impact of the lubricant on the performance of gas coolers has been gaining increasing attention. The existing literature reviews focus on examining the lubricant effect on the heat transfer performance of gas coolers. However, the studies do not present a detailed discussion and a systematic summary of the flow characteristics. The present paper aims to offer an overall review of the lubricant impact on the flow characteristics of CO2 in gas coolers. The authors hope it will help researchers conduct additional research about practically designing and optimizing gas coolers. This paper reveals the flow mechanism by providing critical discussions on how temperature, lubricant type, lubricant concentration, mass flux, operational pressure, tube diameter, and tube configuration influences the flow characteristics of the CO2 -lubricant mixture. Then, the paper summarizes and evaluates the latest developments related to CO2 -lubricant mixture in the flow and heat transfer analysis models and pressure drop correlations. Moreover, the current research gap is summarized, and the study proposes development directions. These include measuring thermo-physical properties of CO2 -lubricant mixture, examining pressure drop characteristics under different tube configurations, developing universal pressure drop correlations, and studying flow characteristics in vertical tubes.